2005
DOI: 10.1515/ijamh.2005.17.3.231
|View full text |Cite
|
Sign up to set email alerts
|

Family-based association study of 5-HT2A receptor T102C polymorphism and suicidal behavior in Ashkenazi inpatient adolescents

Abstract: Suicidal behavior runs in families and is partially genetically determined. Since greater serotonin 5-HT 2A receptor binding has been reported in postmortem brain and platelets of suicide victims, the 5-HT 2A receptor gene polymorphism T102C became one of the candidate sites in the study of suicide and impulsive-aggressive traits. However, studies that examined the association of this polymorphism with suicidality have contradictory results. This study used a family-based method and one homogenous ethnic group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…These findings suggest a potential role of genes involved in processes that may decrease HPA axis sensitivity to feedback or alter cortisol secretion, which is consistent with tentative evidence for associations between genes linked to inflammatory responses and suicidal behaviors in older or mixed-age samples (Clive et al, 2016;Galfalvy et al, 2015;Guintivano et al, 2014). Further, Zalsman et al found associations between MAOA genotypes and STBs among suicidal adolescents presenting at, or admitted to, the hospital (Zalsman et al, 2011), but did not find significant effects for 5-HTR2A (i.e., a serotonergic candidate gene) in another investigation (Zalsman et al, 2005). A recent study found that specific haplotypes within HTR2C and ANKK1-DRD2 genes, which are implicated in serotonergic and dopaminergic pathways, significantly altered risk for suicidal ideation in adolescence depending on individuals' genetic background (Hill, Jones, & Haas, 2020).…”
Section: Geneticssupporting
confidence: 59%
“…These findings suggest a potential role of genes involved in processes that may decrease HPA axis sensitivity to feedback or alter cortisol secretion, which is consistent with tentative evidence for associations between genes linked to inflammatory responses and suicidal behaviors in older or mixed-age samples (Clive et al, 2016;Galfalvy et al, 2015;Guintivano et al, 2014). Further, Zalsman et al found associations between MAOA genotypes and STBs among suicidal adolescents presenting at, or admitted to, the hospital (Zalsman et al, 2011), but did not find significant effects for 5-HTR2A (i.e., a serotonergic candidate gene) in another investigation (Zalsman et al, 2005). A recent study found that specific haplotypes within HTR2C and ANKK1-DRD2 genes, which are implicated in serotonergic and dopaminergic pathways, significantly altered risk for suicidal ideation in adolescence depending on individuals' genetic background (Hill, Jones, & Haas, 2020).…”
Section: Geneticssupporting
confidence: 59%
“…One possible reason for this is the difficulty of obtaining genetic research consents for minors. Two teams in the world have published several articles, the Zalsman et al ( 34 , 68 , 72 ) and the Brent et al ( 15 ) teams.…”
Section: Resultsmentioning
confidence: 99%
“…The authors show that there was no significant allelic association of A218C polymorphism with suicide attempt or other phenotypic measures according to the HRR method (chi-square = 0.094; p = 0.76) and the TDT method (chi-square = 0.258; p = 0.61). In the same population, Zalsman et al ( 68 ) tested T102C polymorphism (5-HTR2A gene) without demonstrating any significant association in allelic distribution between transmitted and non-transmitted alleles. Similarly, there was no significant association of genotype with any of the clinical traits.…”
Section: Resultsmentioning
confidence: 99%
“…However, Prichard et al (2008) failed to observe any significant association between this marker and a range of behaviors including psychosis, agitation, aberrant motor behavior, and depression. No association was found between rs6313 and suicidal behavior in normal subjects (Correa et al 2007), patients with schizophrenia (Ertugrul et al 2004), and suicide attempters (Zalsman et al 2005). The marker G(−1438)A was shown to be associated with increased impulsivity in normal individuals ) and alcoholics (Preuss et al 2001).…”
Section: Serotonin Receptorsmentioning
confidence: 99%